The built environment factors and cycling behaviour in Putrajaya, Malaysia / Norhazlan Haron - Haron, Norhazlan (2023)
Cycling as one of modes of transport in urban and residential areas has been determined as a solution for urban issues such as congestion and traffic conditions in residential area because it reduces the use of motorised vehicles and possesses health benefits factor. Furthermore, it is an active and environmentally friendly mode of travel. However, built environment factors in community seem to be less associated with cycling behaviour. Therefore, this study seeks to explore the built environment factors that influence the cycling behaviour, specifically in Putrajaya. Associations between these factors have been documented as barriers and a compliance for influences on residents for consuming and conducting cycling activity variables. The conceptualisation of variables, measurement of the variables, and examination of relationships between the listed variables has been conducted to determine the most influence-built environment factors for cycling behaviour. The variables are personal characteristics of cycling behaviour, personal factors for health and barriers, and built environment factors. The personal items include the social support aspects such as, socioeconomic factors. Meanwhile, built environment factors include weather, land use form, accessibility, transport safety, and street connectivity. Survey approach was selected for this study through the use of questionnaire. The study was conducted in three selected areas in Putrajaya: precinct 7, 8, and 9. The selected areas were recommended by Perbadanan Putrajaya because they have mix land use within residential area, public facilities, and commercial area. The location for each precinct was also stated as near to workplace. The data population for the selected areas was based on the data of ratepayer record retrieved from the local authority. The list of questions included in the questionnaire covers on personal characteristics, cycling behaviour, built environment, and perception on cycling behaviour. All of the listed questions and variables have been evaluated and validated using a pilot survey and certified by experts amongst the academicians, cycling club members, and local authorities to provide a deeper understanding of the examined issue, soit suitable questions for the survey, and determine the right time frame before conducting the actual survey. Targeted respondents for this study were selected people in Putrajaya that has been active with cycling activity. From the survey, 118 respondents' responses were collected from the members of cycling club, cycling association, and officers of the local authorities. All targeted respondents were active and familiar with cycling activity during weekends or leisure time with their friends or/and family. Through the use of descriptive analysis and after finalising the suitable variables by Factor Analysis, the finding reveals the suitable and reliable factors to make the potential future intervention factors. The listed factors that have been identified to enhance cycling behaviour are individual experiences, impression about built environment, as well as personal and social factors in cycling activity. The implications and recommendation from this research contribute to the existing body of knowledge on cycling behaviour. In addition, the finding of this study can become a point of reference and guidance for policy makers and urban development agencies to design suitable intervention strategies, specifically in terms of intervention at social and physical level for provision of cycling facilities.